Inflation and Trading - Philip Schnorpfeil; Michael Weber; Andreas Hackethal (CESifo GmbH, 2024)
We study how investors respond to inflation combining a customized survey experiment with trading data at a time of historically high inflation. Investors' beliefs about the stock return-inflation relation are very heterogeneous in the cross section and on average too optimistic. Moreover, many investors appear unaware of inflation-hedging strategies despite being otherwise well-informed about inflation rates and asset returns. Consequently, whereas exogenous shifts in inflation expectations do not impact return expectations, information on past returns during periods of high inflation leads to negative updating about the perceived stock-return impact of inflation, which feeds into return expectations and subsequent actual trading behavior.
Keywords: C93; D14; D83; D84; E22; E31; E44; G11; G51; 330; belief formation; field experiment; inflation; trading